Mutation in Neurospora crassa Affecting Some of the Extracellular Enzymes and Several Growth Characteristics - Murayama, Tadako (1973)
A mutant of Neurospora crassa, strain T9, which shows reduced activity of glucoamylase, was isolated. The mutant glucoamylase was not altered in pH optimum, or thermostability, but altered in elution profile of Bio-Gel filtration. The T9 mutation led to other distinct phenotypic effects: a poor growth response, resistance to the effect of sorbose, a high activity of extracellular acid phosphatase, and an increased sensitivity to high osmolarity of the growth medium. The discussion was based on the idea that the T9 mutation occurred at a gene governing the synthesis of cell wall precursors and resulted in an alteration in various characteristics related to extracellular enzymes and growth.